Effects of Pre-exhaustion Versus Traditional Resistance Training on Training Volume, Maximal Strength, and Quadriceps Hypertrophy - Trindade, Thiago Barbosa; Prestes, Jonato; Neto, Leônidas Oliveira; Medeiros, Radamés Maciel Vitor; Tibana, Ramires Alsamir; de Sousa, Nuno Manuel Frade; Santana, Eduardo Estevan; Cabral, Breno Guilherme de A. T.; Stone, Whitley Jo; Dantas, Paulo Moreira Silva (Frontiers in Physiology, 2019)
Background: The pre-exhaustion method (PreEx) is used as a resistance training (RT) method to increase muscle mass, yet the chronic effects of this method are poorly understood. Objective: Although readily prescribed as a resistance training (RT) method for promotion of muscle hypertrophy, few researches give light to gains made after chronic pre-exhaustion (PreEx) RT. Therefore, we compared the effects of traditional versus PreEx RT programs on muscle strength, body composition and muscular hypertrophy in adult males. Methods: Untrained subjects (age: 31.37 ± 6.83 years; height: 175.29 ± 5.52 cm; body mass: 82.04 ± 13.61 kg; 1RM leg press: 339.86 ± 61.17 kg; 1RM leg extension: 121.71 ± 11.93 kg) were submitted to nine weeks of RT with weekly sessions. Traditional (TRT) group (n = 12) performed 3 sets at 45 ° of leg press exercise at 75% of 1RM, PreEx group (n = 12) completed a set to failure on a leg extension machine prior to the leg press, and the control (CON) group (n = 7) did not train. Maximum strength, muscle thickness and body composition were analyzed. Results: PreEx group increased in maximal strength on leg press (16 ± 8%) and leg extension (17 ± 11%), while the TRT group improved by 15 ± 9% and 11 ± 4%, respectively. The thickness of the quadriceps muscles increased for both intervention groups. Specifically, the post-training thickness of the vastus lateralis was significantly higher for PreEx (55%) compared to the CON group. The TRT group presented a greater loss of total and thigh fat mass when compared with the PreEx method. These results were found in the presence a lower training load for the PreEx group. Conclusion: The PreEx training can decrease the total training volume while maintaining results in strength and hypertrophy when comparing to TRT. However, TRT may be optimal if the goal is to decrease fat mass.